PENGARUH MODEL PEMBELAJARAN SDL MELALUI PENERAPAN ARGUMENTATIVE ASSESSMENT DAN CRITICAL THINKING - Ipah Budi Minarti; Atip Nurwahyunani; Sasha Amalia; Devi Oktaviani Safitri, Eka Maya Putri Anggraeni, Muhammad Ilham Sagaf, Imarotul Umamah, Rizky Amali (CV. ADIBA AISHA AMIRA, 2023)
Self-directed learning (SDL) based learning model has received significant attention in an effort to improve students' self-learning ability and critical thinking skills. Self- Directed Learning is an independent learning model that gives students the freedom to identify their learning needs, set learning objectives, find learning resources, select and use learning strategies, and evaluate their learning outcomes. This article shows that the SDL learning model enriched with argumentative evaluation and critical thinking has a significant positive influence on students. The application of argumentative assessment helps students develop analytical skills, logical reasoning, and the ability to build and defend arguments effectively. Meanwhile, the development of critical thinking through SDL learning allows students to take the initiative in identifying, planning and evaluating their own learning. It is important to adopt a learning approach that encourages students to take initiative in their own learning process and actively apply critical thinking skills in learning